IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN IPS (STUDI KASUS DI SMP NEGERI 1 MIRI) - Sarwiyati, S.; Joebagio, Hermanu; Agung S., Leo (HISTORIKA, 2015)
This research aimed: (1) to describe the Social Science teachers’ and students’ knowledge; (2) to analyze the Social Science learning plan and implementation by the teachers; (3) to describe the evaluation of Social Science learning by teachers; and (4) to analyze the obstacles in the implementation of Social Science learning. This research employed a descriptive qualitative method,. The data source employed was informant or resource (Social Science teachers and students), place and event (Social Science learning activity in the class), document and archive (RPP, score book, etc).Techniques of collecting data used were in-depth interview, observation and content analysis. with purposive sampling technique. The data validation was conducted using source, researcher, method and theory triangulations. Technique of analyzing data used was an interactive model.The results of research showed that: (1) the knowledge of teachers and students in SMP Negeri 1 Miri on Curriculum 2013 was sufficiently good but had not been applied maximally; (2) teachers developed RPP (Learning Implementation Plan) inconsistent with Permendikbud RI (Education and Culture Minister of Republic of Indonesia’s Regulation) Number 103 of 2014, scientific approach and student-centered learning had been implemented, discovery learning, problem based learning and project based learning had not been implemented; (3) evaluation of knowledge competency had been conducted but evaluation of attitude and skill competencies had not been conducted maximally; (4) the obstacles in learning lied on teacher motivation, scientific learning with student-centered learning and evaluation of attitude and skill competencies.